A lyophilized cross-linked chitosan gel and a preparation method and application thereof
Patent Information
- Application Number
- CN202611200220.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]在孔结构设计方面,现有壳聚糖冻干凝胶普遍存在功能单一、场景适配性不足的缺陷
本发明采用京尼平与氧化葡聚糖分步交联的双共价交联体系,二者反应速率互补,交联点分布更均匀,相比单一交联剂可显著提升凝胶的力学强度与抗溶胀性能;同时两种交联剂均为天然来源,无有毒化学试剂残留,细胞相容性好,符合医用材料的安全性要求。通过程序化梯度降温工艺,利用冰晶生长动力学差异在单一凝胶内部一体成型分级多孔梯度结构,表层小孔可发挥物理屏障作用,阻隔外界微生物侵入,内部大孔可快速引流创面渗出液、利于营养物质传输与细胞浸润;相比多层复合结构无层间界面,避免了使用中剥离脱落的风险,结构与功能一体化设计更适配创面愈合需求。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical technology, and in particular to a freeze-dried cross-linked chitosan gel, its preparation method, and its applications. Background Technology
[0002] Chitosan, a natural cationic polysaccharide derived from chitin through deacetylation under alkaline conditions, possesses excellent biocompatibility, biodegradability, antibacterial activity, and wound-healing properties, and has been widely used in medical dressings, tissue engineering scaffolds, and drug delivery systems. However, unmodified chitosan exhibits poor mechanical strength and uncontrollable degradation rates in aqueous solutions, limiting its further clinical application.
[0003] However, the current preparation technology of chitosan freeze-dried gel still faces many technical bottlenecks, restricting its further clinical application and industrialization: Regarding the cross-linking system, existing technologies struggle to achieve a balance between mechanical properties and biosafety. While traditional chemical cross-linking agents such as glutaraldehyde and epichlorohydrin can effectively improve the mechanical strength of the gel, they pose a risk of residual cytotoxicity, making it difficult to meet the biosafety requirements of medical materials. Using a single natural or ionic cross-linking agent results in gels with low mechanical strength, prone to excessive swelling or even structural collapse upon contact with water, and with difficult-to-control degradation cycles, failing to meet the needs of long-term wound coverage. Existing dual-cross-linking modification schemes often employ simultaneous addition of cross-linking agents, which easily leads to problems such as localized gelation and uneven cross-linking distribution, resulting in poor molding and processing performance. For example, Chinese patent CN105920679B discloses a skin scaffold material with a three-dimensional gradient pore structure and its preparation method. Using gelatin and chitosan as substrates and genipin as a crosslinking agent, the mixed solution is injected into a specialized mold, and a flat-plate heat exchanger is used for stepped cooling. Directional freezing is achieved by constructing a vertical temperature gradient, followed by freeze-drying to obtain a three-dimensional skin scaffold material with a pore size that gradually decreases from the lower to the upper surface. However, using genipin alone for crosslinking results in limited crosslinking density, leading to insufficient mechanical strength and a relatively rapid degradation rate in humid environments, making it difficult to meet the clinical needs of chronic wounds requiring long-term mechanical support. Furthermore, directional freezing relies on specialized molds and heat exchanger equipment, which have complex structures (requiring an array of conical heat-conducting needles), making process scale-up and equipment cleaning difficult. For example, Chinese patent CN114887108B discloses a sodium alginate / chitosan quaternary ammonium salt double crosslinked medical dressing with a gradient pore structure and its preparation method. Sodium alginate is the main substrate, and its degradation is mainly achieved through ion exchange. The in vivo degradation behavior is uncontrollable, and the degradation products are not endogenous substances in the human body, raising questions about long-term safety.
[0004] In terms of pore structure design, existing chitosan freeze-dried gels generally suffer from limitations in functionality and adaptability to various application scenarios. Chitosan gels produced by conventional freeze-drying processes are mostly homogeneous porous structures: if the overall pore size is small, although it can block the invasion of external microorganisms, its drainage capacity for wound exudate is insufficient, easily leading to adhesion between wound fluid and dressings; if the overall pore size is large, although it possesses good exudate conduction and cell infiltration properties, its physical barrier function is weak, making it difficult to resist the invasion of external bacteria. Existing products with gradient pore structures are mostly prepared using multilayer composite processes, with obvious bonding interfaces between layers. During clinical use, interlayer peeling and detachment are prone to occur, and the preparation process is complex and production efficiency is low.
[0005] Furthermore, existing technologies present inherent contradictions in their preparation processes. When using a cross-linking followed by freeze-drying approach, the viscosity of the system increases significantly after the cross-linking reaction, and ice crystal growth is inhibited during freezing, resulting in a gel with low porosity and poor pore structure regularity. Conversely, when using a freeze-drying followed by cross-linking approach, the pre-prepared porous framework is prone to swelling and collapse during the immersion in the cross-linking agent, severely damaging the pore structure. Multiple washings are required to remove residual cross-linking agent, leading to long production cycles and poor batch stability. Summary of the Invention
[0006] In view of this, the present invention proposes a freeze-dried cross-linked chitosan gel, its preparation method and application, to solve the above problems.
[0007] The technical solution of this invention is achieved as follows: a method for preparing freeze-dried cross-linked chitosan gel, comprising the following steps: S1. Dissolve chitosan in an acidic solution to obtain a chitosan solution; S2. Add a crosslinking agent to the chitosan solution to carry out a crosslinking reaction, and obtain a crosslinked chitosan hydrogel; S3. Pre-freeze the cross-linked chitosan hydrogel by gradient cooling. S4. Freeze-dry the pre-frozen gel to obtain freeze-dried cross-linked chitosan gel.
[0008] Further, in step S1, the degree of deacetylation of the chitosan is 80%~98%, and the viscosity-average molecular weight is 5×10⁻⁶. 4 ~5×10 5 Da.
[0009] Further, the acidic solution is one of acetic acid solution, hydrochloric acid solution, lactic acid solution or ascorbic acid solution, with a concentration of 0.5%~5% (w / v) and a pH of 2.0~5.0; the chitosan solution has a concentration of 1%~5% (w / v).
[0010] Further, in step S2, the crosslinking agent is genipin and oxidized dextran, with a mass ratio of 1:0.5 to 1:3; the total amount of crosslinking agent added is 0.5% to 15% of the mass of chitosan; the crosslinking reaction is carried out under the condition of stirring at 15 to 40°C for 0.5 to 24 hours.
[0011] Furthermore, in step S2, genipin is added before oxidized dextran, and after reacting with genipin for 1-12 hours, oxidized dextran is added and reacted for another 1-12 hours to form a double network cross-linked structure.
[0012] Furthermore, a porogen is added in step S2. The porogen is selected from polyethylene glycol, polyvinyl alcohol, and sodium chloride particles. The amount of the porogen added is 5% to 50% of the mass of chitosan. After freeze-drying in step S4, the porogen is removed by repeated washing and leaching with deionized water to further control the porosity and pore size range of the gel.
[0013] Further, in step S3, the gradient cooling pre-freezing treatment is as follows: first, the temperature is lowered to -20 to -30°C at a rate of 0.5 to 2°C / min, and held for 1 to 3 hours to complete the surface ice crystal shaping and form a fine ice crystal template; then, the temperature is lowered to -50 to -80°C at a rate of 1 to 5°C / min, and held for 2 to 6 hours to complete the internal ice crystal growth and form a larger ice crystal template.
[0014] Furthermore, in step S4, the temperature of the freeze-drying cold trap is -55 to -85°C, and the vacuum degree is 5 to 50 Pa; and it is divided into two stages: First stage: Control the sample temperature at -30~-20℃ and dry for 6~12h. More than 90% of the free water in the system is removed by sublimation. During this stage, the sample is always below the freezing point, the ice crystals do not melt, and the pore structure can be completely preserved. Second stage: Control the sample temperature to rise to 0~10℃ and continue drying for 6~12h to remove bound water, further improving the structural stability and shelf life of the gel.
[0015] A freeze-dried cross-linked chitosan gel was prepared by the above-described method.
[0016] The above-mentioned freeze-dried cross-linked chitosan gel is used in the preparation of medical dressings, which are hemostatic dressings, wound repair dressings, or anti-adhesion materials.
[0017] Compared with the prior art, the beneficial effects of the present invention are: This invention employs a bivalent cross-linking system of genipin and oxidized dextran, with complementary reaction rates and a more uniform distribution of cross-linking points. Compared to a single cross-linking agent, this significantly improves the mechanical strength and anti-swelling properties of the gel. Furthermore, both cross-linking agents are naturally derived, leaving no toxic chemical residues, exhibiting good cell compatibility, and meeting the safety requirements for medical materials. Through a programmed gradient cooling process, a hierarchical porous gradient structure is integrally formed within a single gel, utilizing the differences in ice crystal growth kinetics. The surface pores act as a physical barrier, preventing the invasion of external microorganisms, while the internal macropores facilitate rapid drainage of wound exudate and promote nutrient transport and cell infiltration. Compared to multilayer composite structures, the absence of interlayer interfaces avoids the risk of peeling and detachment during use. This integrated structural and functional design is better suited to the needs of wound healing.
[0018] This invention adopts a process route of "first cross-linking and molding, then gradient freeze-drying". The cross-linked hydrogel has a certain structural strength and is not prone to pore structure collapse during freeze-drying. With the two-stage freeze-drying process, the ice crystal template is completely preserved in the low-temperature sublimation stage and the moisture is deeply removed in the desorption drying stage. The final gel has a regular pore structure and good batch stability. The preparation process is simple, requires no complicated post-processing, and is easy to scale up for production.
[0019] The gel prepared by this invention can adjust the degradation cycle and mechanical properties by adjusting the amount of crosslinking agent, and adjust the pore size distribution by adjusting the gradient cooling program. It can be flexibly adapted to various medical scenarios such as hemostasis, wound repair, and postoperative anti-adhesion, and has broad clinical application prospects. Detailed Implementation
[0020] To better understand the technical content of this invention, specific embodiments are provided below to further illustrate the invention.
[0021] Unless otherwise specified, the experimental methods used in the embodiments of this invention are all conventional methods.
[0022] Unless otherwise specified, all materials and reagents used in the embodiments of this invention are commercially available.
[0023] Example 1 The preparation method of the freeze-dried cross-linked chitosan gel in this embodiment includes the following steps: S1, Weigh out a sample with a degree of deacetylation of 90% and a viscosity-average molecular weight of 1.5 × 10⁻⁶. 5 Add 2g of chitosan from Da to 100mL of 2% (w / v) acetic acid aqueous solution (pH 3.5), stir at room temperature for 6h until completely dissolved, filter through a 200-mesh filter, and degas under vacuum for 30min to obtain a 2% (w / v) chitosan solution. S2. Add 0.06g genipin (3% of the dry weight of chitosan) to the chitosan solution and stir at 25°C for 4h; then add 0.06g oxidized dextran (3% of the dry weight of chitosan, with a mass ratio of genipin to oxidized dextran of 1:1) and continue stirring at 25°C for 4h to obtain a uniform cross-linked chitosan hydrogel. S3. Inject the cross-linked chitosan hydrogel into a square mold and place it in a programmed cooling freezer for gradient pre-freezing: first, cool it to -25℃ at a rate of 1℃ / min and keep it at that temperature for 2 hours to complete the surface ice crystal shaping; then cool it to -60℃ at a rate of 2℃ / min and keep it at that temperature for 4 hours to complete the internal ice crystal growth. S4. Transfer the pre-frozen gel into a vacuum freeze dryer, set the cold trap temperature to -65℃ and the vacuum degree to 10Pa, and dry in two stages: in the first stage, control the sample temperature to -25℃ and dry for 8 hours to sublimate and remove free water; in the second stage, control the sample temperature to rise to 5℃ and continue drying for 8 hours to desorb and remove bound water to obtain freeze-dried cross-linked chitosan gel.
[0024] Example 2 The preparation method of the freeze-dried cross-linked chitosan gel in this embodiment is basically the same as that in Example 1, except that: in step S2, the amount of genipin added is 2% of the dry weight of chitosan, the amount of oxidized dextran added is 4% of the dry weight of chitosan, and the mass ratio of the two is 1:2; the first stage reaction is 3h, and the second stage reaction is 5h.
[0025] Example 3 The preparation method of the freeze-dried cross-linked chitosan gel in this embodiment is basically the same as that in Example 1, except that: in step S1, the mass volume concentration of the chitosan solution is 3%; in step S3, the gradient pre-freezing procedure is: first, the temperature is lowered to -20℃ at a rate of 0.5℃ / min and kept at that temperature for 3h; then, the temperature is lowered to -70℃ at a rate of 3℃ / min and kept at that temperature for 3h.
[0026] Example 4 The preparation method of the freeze-dried cross-linked chitosan gel in this embodiment is basically the same as that in Example 1, except that: in step S2, 0.6g of sodium chloride particles (30% of the dry weight of chitosan) are added as a porogen, and added simultaneously with oxidized dextran and stirred evenly; after freeze-drying in step S4, the gel is immersed in deionized water and washed repeatedly 3 times, 2 hours each time, to leach out the sodium chloride porogen, and then subjected to a second freeze-drying.
[0027] Comparative Example 1 This comparative example is a chitosan lyophilized gel crosslinked with genipin alone. The preparation method is basically the same as that in Example 1, except that: only genipin is added as a crosslinking agent in step S2, and the amount added is 6% of the dry weight of chitosan. The mixture is stirred and reacted at 25°C for 8 hours.
[0028] Comparative Example 2 This comparative example is a conventionally pre-frozen chitosan lyophilized gel, prepared using a method basically the same as in Example 1, except that in step S3, gradient cooling is not used; instead, the hydrogel is directly placed in a -60°C freezer for 6 hours for pre-freezing.
[0029] Comparative Example 3 This comparative example is a chitosan gel prepared by freeze-drying followed by cross-linking, and the preparation method is as follows: 1. Prepare the same chitosan solution as in Example 1, inject it into a mold, pre-freeze it directly at -60°C for 6 hours, and freeze-dry it under vacuum to obtain an uncrosslinked chitosan freeze-dried scaffold; 2. Immerse the freeze-dried support in an ethanol-water solution containing 6% genipin and crosslink at 25°C for 8 hours; remove it and wash it repeatedly with deionized water to remove residual crosslinking agent, and freeze-dry it again to obtain the finished product.
[0030] Performance testing The gels prepared in Examples 1-4 and Comparative Examples 1-3 were subjected to performance tests, and the test methods are as follows: 1. Porosity Test: The ethanol displacement method was used for determination. The dry gel was weighed and recorded as m0, then immersed in anhydrous ethanol until saturated. After removing it and wiping off the surface liquid, it was weighed and recorded as m1. The porosity was calculated using the formula: P=(m1-m0) / (ρ 乙醇 ×V)×100%, where V is the gel volume.
[0031] 2. Pore size distribution test: The cross-sectional morphology of the gel was observed using a scanning electron microscope (SEM), and the average pore size of the surface and interior was statistically analyzed from 20 randomly selected pores.
[0032] 3. Compression modulus test: A universal testing machine was used for compression testing. The sample was a cylindrical sample with a diameter of 10 mm and a height of 5 mm. The compression rate was 1 mm / min. The slope of the stress-strain curve at 10% strain was taken as the compression modulus.
[0033] 4. Equilibrium swelling rate test: Weigh the dry gel and record the weight as Wd. Immerse it in 37℃ pH 7.4 PBS buffer until swelling equilibrium is reached. Remove it, wipe off the surface liquid, and weigh it again, recording the weight as W. s Equilibrium swelling ratio = (W s -W d ) / W d .
[0034] 5. In vitro degradation test: Weigh the dried gel and record the weight as W0. Immerse it in pH 7.4 PBS buffer containing 1 mg / mL lysozyme, and incubate at 37°C with shaking. Periodically sample, wash, freeze-dry, and weigh the gel, recording the weight as Wt. Degradation rate = (W0 - Wt) / Wt. t ) / W0×100%, record the time required for 50% degradation.
[0035] 6. Cytotoxicity test: L929 cells were tested using the MTT assay according to GB / T 16886.5-2017 standard. The relative cell proliferation rate (RGR) was calculated after 24 h of culture to evaluate the cytotoxicity level.
[0036] The test results are shown in the table below:
[0037] Results analysis: Compared with Comparative Example 1, the compression modulus of each embodiment increased by more than 40%, the degradation cycle was significantly extended, and the swelling rate was controlled within a reasonable range. This verifies that the stepwise dual crosslinking system can effectively improve the mechanical strength and structural stability of the gel, and solves the problems of insufficient mechanical strength and excessively rapid degradation of a single crosslinking agent.
[0038] Compared with Comparative Example 2, the embodiment has a significant pore size gradient, with a surface pore size of only 25~41μm, which can effectively block bacterial invasion, and an internal pore size of 170~260μm, ensuring rapid drainage of exudate; while Comparative Example 2 has a uniform pore size, which cannot achieve both barrier and drainage functions.
[0039] Compared with Comparative Example 3, the porosity of the embodiment is increased by more than 15%, the pore structure is more regular, and the cell compatibility is better. Comparative Example 3 has a significantly reduced porosity due to the swelling and collapse of the pore walls during the post-crosslinking process, and the residual crosslinking agent leads to increased cytotoxicity, which verifies the advantages of the process route of the present invention.
[0040] The relative cell proliferation rate in each embodiment was >90%, and the cytotoxicity level was 1, which meets the biosafety requirements for medical implants and contact materials.
[0041] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing lyophilized cross-linked chitosan gel, characterized in that, Includes the following steps: S1. Dissolve chitosan in an acidic solution to obtain a chitosan solution; S2. Add a crosslinking agent to the chitosan solution to carry out a crosslinking reaction, and obtain a crosslinked chitosan hydrogel; S3. The cross-linked chitosan hydrogel is pre-frozen, and the pre-frozen treatment is a programmed gradient cooling. S4. Freeze-dry the pre-frozen gel to obtain freeze-dried cross-linked chitosan gel.
2. The preparation method according to claim 1, characterized in that, In step S1, the degree of deacetylation of the chitosan is 80%~98%, and the viscosity-average molecular weight is 5×10⁻⁶. 4 ~5×10 5 Da.
3. The preparation method according to claim 1, characterized in that, In step S1, the acidic solution is one of acetic acid solution, hydrochloric acid solution, lactic acid solution or ascorbic acid solution, with a concentration of 0.5%~5% (w / v) and a pH of 2.0~5.0; the chitosan solution has a concentration of 1%~5% (w / v).
4. The preparation method according to claim 1, characterized in that, In step S2, the crosslinking agent is genipin and oxidized dextran, with a mass ratio of 1:0.5 to 1:3; the total amount of crosslinking agent added is 0.5% to 15% of the mass of chitosan; the conditions for the crosslinking reaction are: stirring at 15 to 40°C for 0.5 to 24 hours.
5. The preparation method according to claim 3, characterized in that, In step S2, genipin is added before oxidized dextran, and after reacting with genipin for 1-12 hours, oxidized dextran is added and reacted for another 1-12 hours.
6. The preparation method according to claim 1, characterized in that, In step S2, a porogen is added. The porogen is selected from polyethylene glycol, polyvinyl alcohol, and sodium chloride particles. The amount of the porogen added is 5% to 50% of the mass of chitosan. After step S4, the porogen is removed by water washing and extraction.
7. The preparation method according to claim 1, characterized in that, In step S3, the programmed gradient cooling pre-freezing process is as follows: first, the temperature is lowered to -20 to -30°C at a rate of 0.5 to 2°C / min and held for 1 to 3 hours; then, the temperature is lowered to -50 to -80°C at a rate of 1 to 5°C / min and held for 2 to 6 hours.
8. The preparation method according to claim 1, characterized in that, In step S4, the temperature of the freeze-drying cold trap is -55 to -85°C, and the vacuum degree is 5 to 50 Pa; and it is divided into two stages: First stage: Control the sample temperature at -30~-20℃ and dry for 6~12 hours; Second stage: Control the sample temperature to rise to 0~10℃ and continue drying for 6~12h.
9. A freeze-dried cross-linked chitosan gel, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 8.
10. The application of the freeze-dried cross-linked chitosan gel as described in claim 9 in the preparation of medical dressings.
Citation Information
Patent Citations
A preparation method of a skin scaffold material with a three-dimensional gradient pore structure
CN105920679B
A method for preparing a sodium alginate / chitosan quaternary ammonium salt double crosslinked medical dressing with a gradient pore structure
CN114887108B